Development and presence of E. coli in parsley irrigated with domestic waste water treated with solar radiation - Sales, Mariana Alexandre De Lima; Sánchez Román, Rodrigo Máximo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2019)
The objective of this study was to evaluate the influence of solar-treated domestic wastewater (ARD-TRS) on the development of parsley (Portuguese coarse), and to verify and quantify the presence of Escherichia coli in the crop. The experiment, carried out at FCA / UNESP, in Botucatu - São Paulo, consisted of the application of different percentages (0, 25, 50, 75 and 100%) of ARD-TRS in the total irrigation depth. The results obtained were satisfactory, since in general there was an increase in values of plant height, number of stalks, diameter of the largest stalk, clump diameter and mass of fresh and dry matter, and significant differences were observed as function of the percent of ARD-TRS in the total irrigation depth. Thus, it was concluded that the use of different percentages of ARD-TRS in the total irrigation depth had a positive influence on the development of the studied culture, presenting a population of E. coli in irrigation water <100 NMP 100 mL-1 and in cultures ≤ 1,000 NMP 100 mL -1.
Desenvolvimento da cultura e presença de E. coli na salsa irrigada com água residuária tratada por radiação solar
Keywords: Coliforms; Petroselinum crispum; Productivity; SODIS; Water reuse